Urbanization space: social and ecological aspects of safety of playgrounds for children and you - Shushunova, Tatyana N. (Journal of the Belarusian State University. Ecology, 2019)
The results of a sociological study using the methods of visual sociology to study the compliance of children’s playgrounds in Minsk with an orientation towards self-preservation behavior, which was carried out in the context of studying the friendliness of the urban environment to children, are presented. Today, playgrounds for children built according to standard designs do not in many respects meet the criteria of a modern open urban space friendly to children and young people, while the situation of play activities within the city is an indicator of its spatial possibilities in terms of organizing conditions for games, ensuring safety, minimal protection against disease and restricting unhealthy lifestyles.
Keywords: city; urban space; children’s playground; self-preserving behavior; friendliness of the urban environment; visual sociology